A STUDY ON THE POLYMORPHISM OF ADALIA BIPUNCTATA LADYBIRD IN MAYMANA CITY, FARYAB PROVINCE, AFGHANISTAN - Azizullah Niazyar; Shamsullah Hotak; Ghani Dad Saeedi (Techno Agriculturae Studium of Research, 2026)
This research was conducted in the year 1400 (2021) in Maymana city, the center of Faryab province in northern Afghanistan. The sampling area was located within the geographic coordinates of 35° 53' 25.8? to 35° 54' 46.3? N latitude and 64° 44' 11.6? to 64° 49' 15.7? E longitude. Lady beetles (Col.: Coccinellidae), with more than six thousand described species worldwide, are considered important natural enemies of agricultural pests and play a significant role in the biological control of pests such as aphids, whiteflies, scale insects, and plant mites. Despite the considerable climatic and botanical diversity in Afghanistan, available information about the lady beetle fauna of the country is limited. Faryab province, with Maymana as its center, is one of Afghanistan’s important agricultural regions. Considering the ecological importance of lady beetles in biological pest control, this study aimed to investigate the polymorphism of the species Adalia bipunctata in this area. The study was carried out during spring and summer of 1400 (2021), with sampling conducted on cultivated hosts such as peach, pear, and rose, as well as on non-cultivated plants and weeds. Three collection methods were used: insect netting, manual collection, and shaking the host plant onto a white plastic tray. Collected adult insects were preserved either in 70% ethanol or by killing and drying. Identification of specimens was performed using morphological features and examination of the male external genitalia. Different morphs of Adalia bipunctata were distinguished based on morphological traits such as the number, size, and pattern of elytral spots, as well as the color of the elytra and pronotum. Overall, two major morphs and several minor morphs of this species were identified and classified into seven categories.